Cubitus interruptus-independent transduction of the Hedgehog signal in Drosophila. - Gallet, A.; Angelats, C.; Kerridge, S.; Therond, P.P. (Development, 2000)
The Hedgehog (Hh) family of secreted proteins are key factors that control pattern formation in invertebrates and vertebrates. The manner in which Hh molecules regulate a target cell remains poorly understood. In the Drosophila embryo, Hh is produced in identical stripes of cells in the posterior compartment of each segment. From these cells a Hh signal acts in both anterior and posterior directions. In the anterior cells, the target genes wingless and patched are activated whereas posterior cells respond to Hh by expressing rhomboid and patched. Here, we have examined the role of the transcription factor Cubitus interruptus (Ci) in this process. So far, Ci has been thought to be the most downstream component of the Hh pathway capable of activating all Hh functions. However, our current study of a null ci allele, indicates that it is actually not required for all Hh functions. Whereas Hh and Ci are both required for patched expression, the target genes wingless and rhomboid have unequal requirements for Hh and Ci activity. Hh is required for the maintenance of wingless expression before embryonic stage 11 whereas Ci is necessary only later during stage 11. For rhomboid expression Hh is required positively whereas Ci exhibits negative input. These results indicate that factors other than Ci are necessary for Hh target gene regulation. We present evidence that the zinc-finger protein Teashirt is one candidate for this activity. We show that it is required positively for rhomboid expression and that Teashirt and Ci act in a partially redundant manner before stage 11 to maintain wingless expression in the trunk.